Development of Formative Assessment Instruments Misconception Check to Analyze the Conception of Thermodynamics in High School Students - Alvani, Clarinta; Efendi, Ridwan; Zakwandi, Rizki (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
The demands of formative assessment in the kurikulum merdeka should ideally be able to diagnose students’ conceptual patterns in depth. However, common assessment practices are still limited to instruments that only measure correct or incorrect answers, so they cannot reveal conceptual understanding. The gap between these demands and reality has led to the development of more targeted instruments, especially for complex thermodynamics material. This study aims to develop a formative assessment instrument in the form of a misconception check to analyze high school students’ conceptions of thermodynamics. The method used is quantitative with an instrument development approach based on the Mardapi model. The developed instrument is a formative assessment tool in the form of a misconception check with a multiple-choice format, with answer options designed to represent various categories of conceptions. The instrument was tested on 262 students from three high schools, and its validity was evaluated through content validity, construct validity, and readability tests. After a series of evaluations, it was found that 3 items were invalid and were eliminated, leaving 33 items that were suitable for use. This instrument has a unidimensionality value of 21%, an average Aiken's V coefficient of 0.96, and reliability of 0.92. The results of the study indicate that the developed formative misconception check assessment instrument is feasible and effective for analyzing the conceptions held by high school students on thermodynamics material. Therefore, this instrument can help teachers specifically analyze students' conceptions and design targeted learning.